PENERAPAN METODE PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR FISIKA PADA SISWA KELAS XII SMAN 9 PEKANBARU - Ramlah Ramlah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2017)
This research is motivated by the low results for studying physics class XII student of SMAN 9 Pekanbaru. This study aims to improve learning outcomes Physics XII grade students of SMAN 9 Pekanbaru using cooperative learning methods snowball throwing, which is carried out for 1 month. The subjects were all class XII student of SMAN 9 Pekanbaru totaling 36 people. Form of research is classroom action research. The research instrument consists of instruments and instrument performance data collection activity observation sheet form teacher and student activity. Based on the analysis and discussion can be concluded that the application of cooperative learning methods throwing snowball mode can improve learning outcomes physics class XII student of SMAN 9 Pekanbaru in physics. This success is due to the implementation of cooperative learning methods throwing snowball type of activity the students become more active which means that students tend to be positive in following the teaching-learning process provided by the teacher and in discussions within and between groups. Under these conditions, the enrollment rate will increase. The successful implementation of cooperative learning methods type snowball throwing on the subjects of physics, it is known that the learning outcome of the first cycle to the second cycle. In the first cycle of student learning outcomes 41,20% lower with an average of 79,40. While the learning outcomes of students in the second cycle is very high, with an average of 85,80.